Ichthyofauna from tributaries of the Paranapanema River basin, Cerqueira César municipality, southeastern Brazil - F. Tinti; R. Ferrazi; G. Correia-Silva; F. P. Ottoni; M. E. Molina; L. O. Vieira; F. R. Carvalho; L. C. Q. Corazza; C. V. Silva; V. M. Azevedo-Santos (Brazilian Journal of Biology, 2024)
Abstract Here we provide an ichthyofaunistic inventory of the Cerqueira César municipality, in the middle Paranapanema River drainage, upper Paraná River basin, São Paulo State, southeastern Brazil. Collections were carried out in 10 streams and in the Novo River, an important watercourse in the Paranapanema River basin. We caught a total of 808 individuals comprising 49 fish species. Among our main findings—in addition to the high species richness in the sampled region—was the capture of a probably undescribed species of Cambeva and the non-native poeciliid Poecilia reticulata. Some individuals were not identified accurately at the species level, requiring future evaluations. Our study fills an important gap on the ichthyofauna of the municipality of Cerqueira César and may, in the future, assist in new studies on impacts on waterbodies in the studied region.